Development of a Direct Current Electric Circuit Teaching Aid to Improve Students’ Science Process Skills - Pramudita, Finna; Suryadi, Ahmad; Suwarna, Iwan Permana (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
The low level of students' understanding of the abstract concept of direct current electricity, as indicated by daily test scores falling below the Minimum Completeness Criteria, along with their underdeveloped science process skills, forms the background of this study. The main objective of this research is to develop a direct current electric circuit teaching aid to enhance students’ science process skills. The research employed a development model consisting of four stages: (1) preliminary research, (2) prototype development, (3) summative evaluation, and (4) systematic reflection and documentation. This study was conducted at SMA Negeri 87 Jakarta. The results indicate that the teaching aid meets the criteria of feasibility, effectiveness, and practicality in improving students’ science process skills. Based on validation by media experts and subject matter experts, the teaching aid obtained percentage scores of 97% and 98%, respectively, with an average score of 98%, which falls into the very feasible category. A teacher questionnaire assessing the practicality and effectiveness of the teaching aid showed a practicality score of 80% (categorized as practical) and an effectiveness score of 95% (categorized as very effective). Therefore, this direct current electric circuit teaching aid has proven effective in helping students understand direct current electricity concepts and in enhancing their science process skills.